Service providing by local government in Czech republic in the 1999s - Lacina, Karel; Pešta, Josef (Univerzita Pardubice, 1999)
Providing services for citizens is one of the principal tasks of Czech and Moravian municipalities. Both mandatory and facultative services are implemented through several systems, especially by communal enterprices, associations of municipalities and through the cooperation with the private sector. The responsibility of individual municipal bodies for services is explained in the article.
Keywords: Česko; služby; městské orgány; veřejná správa